The Inter-Communal Talks and Political Life in Cyprus: 1974-1983 - Kıralp, Şevki (Journal of History Culture and Art Research, 2020)
This paper conducts historical research on the inter-communal talks and the political life in the two communities of Cyprus from 1974 to 1983. The period covered by the research commenced with the creation of the bi-regional structure on the island in 1974 and ceased with the declaration of Turkish Cypriot Independence in 1983. As this period constitutes an important threshold in the history of Cyprus, it might be argued that observing the political developments it covers is likely to be beneficial for the literature. The research focused on the two communities’ positions in negotiations as well as their elections and political actors. It utilized Turkish, Greek Cypriot and Turkish Cypriot newspapers (and official press releases), political leaders’ memoirs, national archives of USA (NARA) as well as official online documents. Its findings indicate that the two sides could not reach to a settlement mainly due to their disagreements on the authorities of central and regional governments. While the Turkish Cypriot side promoted broader authorities for the regional governments, the Greek Cypriot side favoured broader authorities for the central government. On the other hand, while Turkish Cypriot leader Denktaş had managed to unite the majority of Turkish Cypriot right-wing voters, the Greek Cypriot right-wing was divided among supporters of Makarios and Clerides. On the other hand, while the Greek Cypriot left-wing was in cooperation with Makarios, the Turkish Cypriot left-wing opposed Denktaş’s policies.